Enhancing A B2B Marketing Strategy in Engineering Consulting Service: A Case Study of PT EMKA Rekayasa Energi - Raditya Ova Triandi (Scieclouds Publishing, 2026)
This study examines how PT EMKA Rekayasa Energi can enhance its business-to-business marketing strategy in the engineering consulting service industry. EMKA has strong technical expertise, project experience, and client trust, especially in energy and electricity-related projects. However, its marketing activities remain largely informal, relationship-based, and dependent on existing professional networks. This condition limits the company’s visibility, client acquisition process, and long-term business development potential. This research uses a qualitative single-case study approach to explore EMKA’s internal capabilities, external market pressures, client expectations, and strategic marketing gaps. Data were collected through semi-structured interviews, written client responses, field notes, internal company information, and secondary data. Five respondents were selected through purposive sampling, consisting of two internal management representatives and three client representatives from different project contexts. The data were analyzed using thematic analysis and supported by Porter’s Five Forces, PESTLE, competitor analysis, customer analysis, RBV VRIO, STP, Marketing Mix 9P, SWOT, and TOWS frameworks. The findings show that EMKA’s main strength lies in technical credibility, responsiveness, field experience, and independent judgment. However, the company still faces weaknesses in digital visibility, proposal standardization, client mapping, portfolio communication, and internal marketing routines. The study proposes a structured B2B marketing strategy focused on market visibility, standardized communication materials, systematic relationship management, digital presence, and internal business development capability. These strategies are expected to reduce dependence on limited client networks, improve proposal competitiveness, expand market reach, and support sustainable growth in the engineering consulting market.